2019
DOI: 10.1177/0018726718819055
|View full text |Cite
|
Sign up to set email alerts
|

Examining the inverted U-shaped relationship between workload and innovative work behavior: The role of work engagement and mindfulness

Abstract: Is workload good or bad for employee innovation? Workload and innovative work behavior are widely studied research topics. However, the relationship between them is not well understood. As a result, there is a lack of evidence-based knowledge that could inform managers and organizations on how to boost workplace innovation in demanding work contexts. Building on the job demands–resources model, the present study posits that workload relates to innovative behavior through work engagement. Specifically, we argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 91 publications
(145 reference statements)
11
147
1
6
Order By: Relevance
“…On the other hand, supervisor’s organizational embodiment was introduced only as one of many boundary conditions in the relationship between leader humor and work engagement. However, many previous studies have indicated that other variables, such as mindfulness ( Montani et al, 2020 ), personal need for structure ( Pundt and Venz, 2017 ), work meaning ( Cai et al, 2018 ), and work autonomy ( Li et al, 2019 ), could moderate the relationship between leader humor and employees’ actions. Hence, future researches could go further by incorporating other moderating variables to examine the boundary conditions of the relationship between leader humor and employee work engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, supervisor’s organizational embodiment was introduced only as one of many boundary conditions in the relationship between leader humor and work engagement. However, many previous studies have indicated that other variables, such as mindfulness ( Montani et al, 2020 ), personal need for structure ( Pundt and Venz, 2017 ), work meaning ( Cai et al, 2018 ), and work autonomy ( Li et al, 2019 ), could moderate the relationship between leader humor and employees’ actions. Hence, future researches could go further by incorporating other moderating variables to examine the boundary conditions of the relationship between leader humor and employee work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In a word, if employees dare to face various problems at work and devote themselves to searching for solutions, their creativity will be fully stimulated ( Pieterse et al, 2010 ). The focus and persistence in this process will bring out more ideas and breakthroughs ( Montani et al, 2020 ), while constantly motivating individuals to practice, thus exhibiting a high level of innovative behavior. That is to say, employees with high work engagement can fully mobilize the resources around them to meet the challenge encountered in their jobs with enthusiasm.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As a special intangible resource, it has become one of the highlights among many factors affecting the occurrence of enterprises. It is a core psychological element beyond human capital and social capital and can promote personal growth and performance improvement (Chen, 2020;Montani et al, 2020). Therefore, in actual business operation, it is very important to pay attention to the development of psychological capital of leaders and employees.…”
Section: Introductionmentioning
confidence: 99%
“…In most empirical identification of U-shaped relationships, researchers will include a nonlinear (usually quadratic) term in a standard linear regression model [ 36 , 37 , 38 ]. If this term is significant, and the estimated extreme point is within the data range, it is considered that there is a U-shaped relationship.…”
Section: Methodsmentioning
confidence: 99%